Assessing the technical efficiency of Malaysian cocoa production - Harun, Harnie (2011)
The growth of the cocoa upstream industry is considered relatively slow, largely because of the continuous decline in the cocoa output. The rate of decline in the cocoa output was 74.2% on the average between 2000 and 2009, thus requiring serious measures that should be undertaken to safeguard the cocoa production sector. Malaysia’s cocoa production structure, which is currently comprised largely of smallholders, faced with a challenge on improving the productivity to increase the production. Due to this, the key of addressing the challenges of increasing the cocoa production in Malaysia is to focus on the efficiency in the cocoa smallholding sector. This study is conducted to determine the efficiency of cocoa production in Malaysia and to analyze the contributing factors to the efficiencies, particularly among the cocoa smallholders. This study will also serve as a guideline for the industry in recommending strategies to be adopted to improve the smallholdings sector. The Stochastic Frontier production approach was used to measure the level of efficiency in this study due to its consistency with theory, relative ease of estimation as well as versatility. The empirical model employed in this study is the Cobb-Douglas as a frontier production function. It was found to be suitable in representing the sampled data and gave better estimates of technical efficiency than the Translog model. The results indicated that variance caused by variables of technical inefficiency is larger than the variance caused by the uncontrolled factors related to the production process. The average computed technical efficiencies for Peninsular Malaysia was 0.47, while in Sabah was 0.44 and Sarawak, 0.20. The large efficiency differentials among these cocoa smallholders were an indication of a substantial potential for efficiency improvement in the cocoa production in the three regions. The economic implication of the study reveals that efficiency among the cocoa smallholders in Peninsular Malaysia could be increased by 53%, followed by Sabah (56%) and Sarawak (80%). From the findings, it can be concluded that there exist a high level of technical inefficiency of about 63 percent, which implies that input utilization is far below the optimum level. There is also a need to introduce a higher-level of technology, planning and training to improve resource allocation as well as adopting the technology of best-practiced farm. The extension services, which are currently implemented should be enhanced and improved as these services is a significant role in improving technical efficiency in the cocoa production in Malaysia. Increasing efficiency of the cocoa production may encouraged the increase in capital investment hence influence more people to invest in the cocoa planting as well as stimulate growth of cocoa production in Malaysia.